The mobiledna (digital narrative approach) : supporting collaborative creativity in mobile moving media production - Arnedillo-Sánchez, Inmaculada (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2009)
Collaboration and creativity are beneficial for learning. While collaboration involves conflict, articulation and co-construction, creativity banks on the interplay between divergent and convergent thinking. Collaborative creativtity requires developing common understanding, engaging in discussion, and sharing knowledge resources. Moving media production engenders opportunities for collaboration, and encourages creativity and self-expression. However access to technology, time investment, and the lack of pedagogical methodologies, are impediments for the adoption of the activtity as a teaching and learning tool.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.